Formulation And Evaluation Of Instant Drink Powder Preparation With A Combination Of Vitamin C And Zinc Sulfate Monohydrate - Faneshia Nabil Ayushita; Halyza Nada Kirana; Embun Larasati Kuncoro; Fauzi Rizki Fadhilah; Zefanya Yoga Permana Purba (CV. AFDIFAL MAJU BERKAH, 2026)
Vitamin C and Zinc Sulfate Monohydrate is a combination of active substances that play a role in improving the immune system and maintaining body health. This research aims to create a powder formulation of a combination of vitamin C and zinc sulfate that is safe for consumption. Vitamin C is a very sensitive substance and can be degraded into dehydroascorbic acid due to photooxidation and hydrolysis reactions. Vitamin C is easily degraded in aqueous media, at high pH, ​​high temperatures, in the presence of oxygen and metal ions. Formulation in solid form such as powder is often chosen to increase the chemical stability and shelf life of vitamin C. Formulation of vitamin C and zinc in powder form also provides convenience for consumers who have difficulty swallowing in pill, tablet, or capsule form. The evaluation results showed that the preparation had good characteristics in most parameters, including white color, smooth texture, odorless, slightly sweet and sour taste, particle size of 0.7795 mm, flow time of 10 seconds, water content of 2.73%, angle of repose of 31.52°, dissolution time of 1 minute 29 seconds, bulk density of 0.64, tap density of 0.72, Hausner ratio of 1.12, and compressibility index of 11.11%. However, the preparation did not meet the requirements for particle size distribution due to the excessive number of fines and a pH value of 3.57 which was below the specified range (4–7). Therefore, the resulting formulation still requires further optimization to improve compliance with the preparation quality standards.